Efeito de soluções desinfetantes sobre a estabilidade de cor de botões de íris artificiais nas cores azul e marrom obtidos por diferentes técnicas - Menezes, Fernanda Bimbato de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The color of the artificial iris with acceptable aesthetic is an important clinical condition for the rehabilitation of the eye. So, the present study was to investigate the influence of three disinfectant solutions on the color change of the artificial iris button obtained by different techniques for two-tone color. A total of 300 samples will be made by simulating artificial eyes. Samples were fabricated with either blue or brown color artificial iris. For each color, fifty samples of each technique (conventional (CE), prefabricated cap technique (PC) and inverted painting (IP)) will be made. For each technique, 10 samples will be subjected to three types of disinfectant solution (soap (NES), Opti-Free (OPF) and chlorhexidine 4% (CHX)), or remained without disinfection (control 1 (C1) will be immersed in saline and control 2 (C2) will be subjected to dry conditions). The disinfection procedure was performed during 120 days, and the disinfected samples were stored in saline solution during this period. The artificial iris color measurement was conducted through reflection spectrophotometry using the CIE L * a * b * after prosthesis polymerization, and after 60 and 120 days. The color change values increased over time. For both colors, ANOVA reveled significant difference on the color change values of the artificial iris button among technique and period; and disinfectant and period (P<0.01). CE e PC exhibited highest color stability for both color artificial iris. The artificial iris buttons disinfected with CHX exhibited highest color change significant compared to others disinfectants and control groups, independent the color. In conclusion, technique and disinfection/storage periods affected the artificial iris button

A cor da íris artificial com estética aceitável é uma importante condição clínica para a reabilitação ocular. Dessa forma, este estudo teve como propósito avaliar a influência de três soluções desinfetantes, na alteração de cor do botão de íris artificial obtido por diferentes técnicas, para duas tonalidades de cor. Foram confeccionadas 300 amostras simulando próteses oculares, sendo metade dessas amostras com íris artificial na cor azul e a outra metade na cor marrom. Para cada cor, cinquenta amostras de cada técnica empregada (técnica convencional (PE), técnica com calota pré-fabricada (CA) e pintura invertida (PI)) serão confeccionadas. Para cada técnica empregada, 10 amostras foram submetidas a três tipos de soluções desinfetantes (sabão neutro (NES), Opti-Free (OPF) e clorexidina a 4% (CHX)); ou permanecerão sem desinfecção (C1, imersas em soro fisiológico e C2 restritas a ambiente seco).A desinfecção foi realizada por 120 dias, sendo as amostras desinfetadas, armazenadas em soro fisiológico durante esse período. Os valores de alteração de cor aumentaram ao longo do tempo. Para ambas as cores, ANOVA mostrou diferença estatística significante nos valores de alteração de cor do botão de íris artificial entre técnica e período; desinfetante e período (P<0,001). As técnicas PE e CA apresentaram maior estabilidade de cor, para ambas as cores de íris artificiais.Os botões de íris artificial desinfetados com CHX apresentaram maiores valores de alteração de cor, significante, em relação aos outros desinfetantes e grupos controle, independente da cor. Em conclusão, a técnica e desinfecção/período de armazenagem influenciaram na estabilidade de cor do botão de íris artificial
Keywords: Desinfecção; Cor; Espectrofotometria; Resinas acrílicas; Olhos artificiais; Disinfection